2002
DOI: 10.1021/ic010779t
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Energy Self-Exchange with Macrocyclic Chromium(III) Complexes

Abstract: The luminescence lifetimes of N-deuterated Cr(III) complexes of macrocyclic tetraamine ligands, trans-CrN(4)X(2)(n)()(+), are substantially longer than those of their undeuterated counterparts in room temperature solution. Thus, excited-state emission quenching of the longer lived species by the shorter lived species may be studied by analyzing the decay profile following pulsed excitation. Flash photolysis experiments were carried out for three deuterated/undeuterated pairs of trans-CrN(4)X(2)(n)()(+) complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The prospect of inventing functional photochemical molecular devices (PMDs) , has prompted research on intramolecular energy transfer between transition metal centers bridged by ligands that facilitate such electronic communication . We have had a long-term interest in the preparation and photophysical characterization of trans -Cr(N 4 )(CN) 2 + (where N 4 = a tetraazamarocyclic ligand) complexes and in the study of the rates of intermolecular electronic energy transfer between them . Our interest in the alkynyl ligands stems from their promise as isoelectronic substitutes for the CN – ligand and the possibility of preparing photoactive complexes with bridging alkynyl ligands that might mediate intramolecular electron- and energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The prospect of inventing functional photochemical molecular devices (PMDs) , has prompted research on intramolecular energy transfer between transition metal centers bridged by ligands that facilitate such electronic communication . We have had a long-term interest in the preparation and photophysical characterization of trans -Cr(N 4 )(CN) 2 + (where N 4 = a tetraazamarocyclic ligand) complexes and in the study of the rates of intermolecular electronic energy transfer between them . Our interest in the alkynyl ligands stems from their promise as isoelectronic substitutes for the CN – ligand and the possibility of preparing photoactive complexes with bridging alkynyl ligands that might mediate intramolecular electron- and energy transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic energy transfer between transition metal complexes often involves spin and symmetry forbidden transitions and thus proceeds through the exchange mechanism, prompting the application of Marcus−Hush theory in order to understand the reaction dynamics. , A number of studies of energy transfer have been analyzed to determine the relative importance of thermodynamics, electronic factors, and nuclear factors in these bimolecular reactions. The majority of these studies have involved Cr(III) donor and/or acceptor molecules due to the large body of existing knowledge on Cr(III) photophysics and photochemistry , Our interest in this area is to discover systems for which energy transfer self-exchange can be studied so that cross-exchange and self-exchange dynamics can be compared in a manner similar to what has been done for electron transfer . Several investigations of reactions approximating energy transfer self-exchange utilized a method first described by Maharaj and Winnik involving flash photolysis of mixtures of cleverly designed chromophores. The chomophores are designed such that slight structural modifications substantially affect the excited state lifetime of the molecule but leave the electronic energy levels relatively unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes have also demonstrated a remarkable increase in their excited-state lifetimes upon N-deuteration. , Extensive studies of these types of complexes by Endicott and co-workers have been directed toward determining the effect that stereochemical alterations have on excited-state characteristics with the goal of being able to design ligand systems to produce desired excited-state behavior. , Several other groups have also taken advantage of the photobehavior of these types of complexes. Recently, we have shown that energy-transfer self-exchange rate constants can be measured or bracketed with the complexes trans -[Cr(cyclam)(NH 3 ) 2 ] 3+ , trans -[Cr(cyclam)(CN) 2 ] + , and trans -[Cr(tet a)F 2 ] + by monitoring exchange between the longer lived deuteriocomplex and the shorter lived protiocomplex . Additionally, Ford et al have shown that the nitrito complexes of Cr(III) cyclam undergo reversible NO photolabilization, a fact attributed to the suppressed amine labilization of cyclam …”
Section: Introductionmentioning
confidence: 99%